Bioconversion of sago waste using aspergillus sp. For the production of reducing sugars - Tan, Wei Ling (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this study was to explore the possibility of utilizing sago hampas to convert them into reducing sugars using microbes in solid state fermentation (SSF). Microbial consortium represents a crucial new frontier for biotechnology. Hence, in this study three different types of Aspergillus sp. was used to investigate their production of reducing sugars and soluble proteins. Mono cultures, co-cultures and mixed cultures of Aspergillus niger PANI, Aspergillus flavus NSH9 and Aspergillus versicolor FP13 were evaluated for their potential performance in producing reducing sugars. This was then followed by further optimization of the selected cultural conditions with the following variables such as incubation period (days), pH, effect of nitrogen supplementation and temperatures, :C. Supernatants of extracted were used to estimate reducing sugars using dinitrosalycilic acid (DNS) and crude protein using Bradford methods. Among the seven different culture combinations, co-culture ofAspergillus niger PAN I and Aspergillus vesicolor FP 13 produces the highest amount of reducing sugars of (0.786±0.05 mg/mL) and soluble protein of (0.070±0.00mglmL). The optimum incubation period, temperature and pH for maximum reducing sugar and soluble protein production were at 6 days, pH 4.0 and 35:1C. Among the four different nitrogen sources used, ammonium nitrate 0.1 % (w/w) gave the highest production of reducing sugars and soluble protein. From this study, it was deduced that, co-cultures of Aspergillus sp. gives higher yields of reducing sugars then compared to pure and mix cultures. Apart from that there is a significant increase in the reducing sugars production under the optimized conditions as compared to control.